Does Perceiving the Authentic Self Affect the Meaning of Life? - Febrianti, Rianda; Ginanjar, Adriana S. (Jurnal Psikologi, 2024)
Self-authenticity and the meaning of life are important for an individual’s psychological well-being. However, studies on the relationship between authenticity and the meaning of life using a quantitative approach have been largely carried out in Western countries, with minimum research being conducted in the Indonesian context. However, several studies have found differences in self-authenticity among different social and cultural conditions. The purpose of this study was to unveil the influence of perceived authenticity on the meaning of life by controlling for self-esteem and positive affect in Indonesian adults. These control variables were added to see the influence of the two variables more precisely. This study involved 369 adult Indonesians (aged 18-64 years old, M=32.2 years). The instruments used were the Authenticity Scale, Multidimensional Existential Meaning Scale, Positive and Negative Affect Schedule, and Rosenberg Self-Esteem Test. Data collection was carried out online, and multilevel regression analysis was used to test the hypothesis. The findings indicate that, by controlling for self-esteem and positive affect, feeling authentic influences the person’s meaning in life. Perceived authenticity in the 18-35 age group is lower than in the 36-45 and 46-55 age groups. The study also found that the married group perceives themselves as more authentic than the unmarried. The findings of this study can be a basis for future studies on authenticity in Indonesia and help build awareness about the importance of authenticity for Indonesian adults.